Application of Intraoperative Optical Coherence Tomography Technology in Anterior Segment Surgery. (8th April 2022) - Han, Sang Beom; Liu, Yu-Chi; Mohamed-Noriega, Karim; Mehta, Jodhbir S.
Abstract : The use of optical coherence tomography (OCT) technology in anterior segment diseases allows for precise assessment of the changes following anterior segment surgery. Advances in microscope-integrated OCT systems have allowed the utilization of intraoperative OCT (iOCT) in anterior segment surgeries, i.e., cornea, cataract, and refractive surgery. iOCT has enabled real-time precise visualization of anterior segment tissues as well as interactions between surgical instruments and ocular tissue; thus, the device can facilitate surgical procedures and provide valuable information for decision-making during anterior segment surgeries. In this review, the authors will introduce studies regarding the development of iOCT technology and its application in various anterior segment surgeries. Multiple studies have shown the efficacy of the iOCT for intraoperative assistance and guidance, suggesting the potential of the device for optimizing the surgical outcomes after cornea, cataract, and refractive surgery.